Zwitterionic surface grafting of epoxylated sulfobetaine copolymers for the development of stealth biomaterial interfaces. (August 2016) - Chou, Ying-Nien; Wen, Ten-Chin; Chang, Yung
Graphical abstract: Abstract: Most biomaterials have a lack of a simple, efficient and robust antifouling modification approach that limits their potential for biomedical applications. The challenge is to develop a universal surface grafting solution to meet the antifouling requirement. In this work, a new formulation of zwitterionic sulfobetaine-based copolymer, ploy(glycidyl methacrylate- co -sulfobetaine methacrylate) (poly(GMA- co -SBMA)), is designed as a chemical for grafting onto material and is introduced for the surface zwitterionization of versatile biomaterials, including ceramic, metal, and plastics. The grafting principle used to stabilize the poly(GMA- co -SBMA) on the target surfaces is based the base-induced ring opening reaction between epoxied and hydroxyl groups. A universal surface modification procedure was developed and performed from an optimized sequence of ultra-violet ozone pretreatment and trimethylamine-catalyzed zwitterionization on a selective case of versatile surfaces including silicon wafer, ceramic glass, titanium, steel, and polystyrene. The prepared poly(GMA- co -SBMA) with an optimum PGMA/PSBMA ratio of 0.23 and a molecular weight of 25 kDa exhibited the best resistance to fibrinogen adsorption with over 90% reduction as well as blood cell activation, tissue cell adhesion and bacterial attachment on the zwitterionic copolymer grafted surfaces. The developed antifouling grafting introduces a universal modification method to generate zwitterionic interfaces on versatile biomaterial substrates, providing great potential for application in medical device coating. Statement of Significance: A simple, efficient and robust antifouling modification approach is critical for many scientific interests and industrial applications. In current stage, the existing available zwitterionic modifications suffer from the lack of universal surface grafting solution to achieve the antifouling requirement on versatile biomaterial substrates. In this study, we synthesized and characterized a new zwitterionic sulfobetaine-based copolymer, ploy(glycidyl methacrylate- co -sulfobetaine methacrylate) (poly(GMA- co -SBMA)), which is designed as chemical grafting onto material and introduced for the surface zwitterionization of versatile biomaterials, including ceramic, metal, and plastics. This research have a promising opportunity for the application of stealth biomaterial interfaces on the next generation of medical devices.